A study on maintenance management at private school and public school in Malacca / Mohd Hasrul Mahmud - Mahmud, Mohd Hasrul (Faculty of Architecture, Planning and Surveying, 2009)
Maintenance is the continuous protective care of the fabric, contents and setting of a place. A maintenance plan is the most cost-effective way to ensure the ongoing value of any asset, particularly a registered place. The plan should include regular inspections, prompt attention to repairs and a cleaning program. Realizing the importance of maintenance in Malaysia, this dissertation which titled ‘A Study on Maintenance Management at Private School and Public School’ is documented This research comprise of 6 chapters. This research intends to identify how the maintenance management was carried out at Private School and Public School in Malacca. Case studies on three private school and public school that are located in Malacca area were undertaken which is for private school were Kolej Yayasan Saad, Sekolah Madhad Ar-Rahmah and Sekolah Madrasah Ar-Rahmah. For public school were on SMK Tinggi Perempuan, SMK Camossa Convent and SMK Seri Mahkota. Analysis for this research comprise of comparative and descriptive approach as well as statistical analysis which are based on case studies and questionnaire survey. For the finding from the questionnaire and interview with the related person, it determined that for the public school, the maintenance management were carried out by Pejabat Pelajaran Daerah(PPD) party and for private school were carried out by own(school) which is there have a department to do the maintenance management in the school.